Influence of hydrothermal treatment on selenium emission-reduction and transformation from low-ranked coal. (10th September 2020) - Ullah, Habib; Chen, Baoliang; Shahab, Asfandyar; Naseem, Faiza; Rashid, Audil; Lun, Lu; Yousaf, Balal; Khan, Sangar
Abstract: One of the key environmental limitations in coal usage is selenium emission whose removal is focused in this study. We employed hydrothermal treatment to remove Se element and upgrade low rank Huainan coal at 200–300 °C. Pyrolysis temperature given during coal treatment was evaluated to simulate coal transformation into high-rank industrial grade by emphasizing O/C ratio, removal of oxygen functional groups and moisture and chemical structure stability. Following hydrothermal treatment, different characterization techniques including XPS, FTIR, XRD and Raman spectroscopy were used to determine the chemical structure of coal. Findings revealed that hydrothermal treatment process has an important influence on the crystalline structures of low rank coals. The results of XRD and Raman spectroscopy analysis demonstrated much graphitized and aromatic microcrystalline structure. The chemical structure developed was orderly, stable and dense. Selenium XPS spectra comprising of 3D peaks has confirmed several oxidation states including selenide, selenates and oxide species. The removal proportion of Se was significant and increased up to 50.7% with increased HTT temperature (300 °C). This study provides some unique findings pertaining to solubility of sub-critical water and rate of change in pyrolysis temperature as determinant factors in the removal of Se. Our simulation model further concludes that transformation of low rank coal into high rank is a function of temperature treatment coupled with optimization of fixed carbon. We infer that hydrothermal treatment derived coal possesses sufficient lucid attributes to be considered as environmentally safe fuel. Graphical abstract: Image 1 Highlights: Huainan LRC was upgraded by HTT upgrading approach. Aliphatic carbons in LRC decreased while aromatics increased after HTT process. XPS spectra confirmed multiple oxidation states (selenide, selenates, oxides). HTT influence in terms of Se removal was revealed in LRC.